The concept and implementation of an energy retaining wall of large diameter piles - Bujor Octavian (E3S Web of Conferences, 2020)
Performance and success of energy geostructures systems are already facts proven by research and practice. The number of implementations is in constant grow and due to their advantages, such systems have started to be implemented in a variety of structural elements. Among the various types, energy piles are the most common type of energy geostructures. However, most of the existing research, experimental sites and case studies refer to energy piles as a foundation element. This paper presents the concept and implementation steps of a different type of energy piles system which is a retaining wall of piles built in Cluj-Napoca, Romania. The paper is based on a real project case study, where large diameter piles are used as retaining wall for an urban excavation on a steep slope with high slope failure potential. The piles from the retaining system have been energy equipped in order to be used as an energy exchange element with the ground for heating and cooling demand of 3 new residential buildings from the same site. The paper will present the concept of an urban energy retaining wall and implementation stages of the project.